VIRGINA BRINDIS DE SALAS: NOTES ABOUT A BIOGRAPHY - Pinheiro Cantuario, Victor Andre [UNESP]; Marques, Fabiana Pereira (Univ Estadual Mato Grosso Sul, 2020)
This paper presents remarks about the biography of Virginia Brindis de Salas, contemporary afro-uruguayan poet, to contribute to the deconstruction of some wrong points of view about her which assert things she didn't, and on the other hand try to dispute that she is the real author of the two books published under her name. The revision of these errors intents to clarify, even though partially, details about her life and work, following Lewis (1983; 2003) and Young (1991; 1993; 2002; 2003; 2004). To do this, it was consulted Nuestra Raza, Accion, Rumbos, Orientacion, and Revista Uruguay, afro-uruguayan journals available on the Colecciones Digitales from the Biblioteca Nacional de Uruguay's web page, where Salas published poems and was reported. Considering that information, the paper expects to move a step forward in Salas' biography that during her public life, and mainly after her death has been object of constant attempts of discredit and discrimination, as it intends to show.
Keywords: Virginia Brindis de Salas; Afro-Uruguayan Poetry; Female Poetry; Latin American Literature